A Review Study on 4G Security (International Journal of Innovative Research in Computer Science & Technology, 2021)
The introduction of the Long Term  Evolution (LTE) technology in recent technologies has  revolutionized Fourth Generation, 4G Network  communication, allowing users to receive high-speed data  up to 100 MHz. The problem of cyber-security has become  a menace to consumers all around the globe. This article  will go through the LTE security concept. The next  generations of wireless networks, known as 4G, will  completely replace 3rd generation networks. It will provide  faster speeds and multimedia services that are entirely IP based. 4G refers to an integrated, worldwide network that  will give customers with phone, data, and streaming  multimedia services "Anytime, Anywhere." The smooth  handoff, mobility management, security, and service across  multiple integrated networks are all essential and  demanding issues in 4G. Data security, hardware security,  and user privacy and integrity are the most important  security concerns for any wireless mobile device. Security  flaws may be created by attackers or induced by incorrect  device or network parameter settings. The paper explains  the concept of security and why it is important to pay  attention to it. This paper examines what 4G network  technology is and some of the proposed solutions in order  to fully understand the benefits and problems of  successfully deploying 4G. The future aspects are this  Network access security, which allows users to access the  service in a safe and secure manner.
Keywords: Data Security; Internet; Long Term Evolution; Networks; Security; Wireless Network